Clinicopathological and prognostic profile of non-smoking and non-drinking head and neck cancer patients: a population-based comparative study - Bonetti Valente, Vitor [UNESP]; Mantovan Mazzon, Bruna [UNESP]; Urbano Collado, Francisco [UNESP]; Conrado Neto, Sebastião [UNESP]; Lúcia Marçal Mazza Sundefeld, Maria [UNESP]; Ricardo Biasoli, Éder [UNESP]; Issamu Miyahara, Glauco [UNESP]; Galera Bernabé, Daniel [UNESP] (Elsevier, 2022)
Tobacco and alcohol consumption are the main risk factors for head and neck cancer (HNC). However, some individuals do not have a history of addiction and even so they develop the disease. This study evaluated clinicopathological and prognostic features of non-smoking and non-drinking (NSND) HNC patients. A sample of smoking and/or drinking (SD) HNC patients was used to explore the differences with NSND patients. Data were obtained from 667 patients with squamous cell carcinoma in oral cavity, oropharynx or larynx. The group of NSND individuals represented 12.6% of the HNC patients and had higher prevalence of women and elderly compared to SD group. Among NSND patients, most of them displayed tumors in oral cavity, advanced clinical staging and absence of second primary tumor. NSND HNC patients had higher tumor recurrence and increased overall and specific survival rates at 5-years follow-up. The NSND group showed higher prevalence of tumors in lips and alveolar ridge, lower rate of tumors in floor of mouth and no tumor in soft palate. NSND patients show a distinct profile from that found in SD patients. Clinicopathological features from NSND patients should be considered for HNC management.
Keywords: Alcohol; Clinicopathological features; Head and neck cancer; Larynx cancer; Oral cancer; Oropharynx cancer; Prognosis; Risk factors; Smoking; Tobacco